Literacy development in children with cochlear implants: a narrative review. Issue 1 (2nd January 2022) - Bell, Nicola; Angwin, Anthony J.; Wilson, Wayne J.; Arnott, Wendy L.
ABSTRACT: There exists a substantial body of research to suggest that children with cochlear implants (and hearing loss more generally) experience difficulties when learning to read and write. These difficulties are posited to stem partly from limitations in phonological processing ability, which is considered fundamental to typical literacy development. This paper comprises a narrative review of the current literature on (1) literacy development in children with hearing loss and cochlear implants; (2) relationships between literacy sub-skills in children with hearing loss and cochlear implants; and (3) factors that influence learning and contribute to the heterogeneity of the population of children with hearing loss.